Internal Auditors’ Perceptions on Whistleblower Intentions for Fraud Prevention.: Persepsi Auditor Internal terhadap Niat Pelapor Pelanggaran dalam Pencegahan Penipuan. - Sholihah, Amilatus; Biduri , Sarwenda (Indonesian Journal of Innovation Studies, 2025)
General Background: Whistleblowing plays a crucial role in detecting and preventing fraud within organizations, yet internal auditors often face ethical and psychological barriers in fulfilling this responsibility. Specific Background: In Indonesia, fraud cases persist across sectors, and limited protection systems for whistleblowers reduce reporting willingness. Internal auditors, who are central to internal control and fraud detection, need both structural and moral support to act as effective whistleblowers. Knowledge Gap: Previous studies focused mainly on whistleblowing intentions based on individual traits or organizational culture, leaving limited understanding of how internal auditors perceive their role in fostering whistleblowing. Aims: This study explores internal auditors’ perceptions of whistleblower intention factors and their functional role in increasing whistleblowing for fraud prevention. Results: Findings indicate that confidentiality assurance, strong internal control, and leadership commitment significantly strengthen auditors’ intention to report fraud. Novelty: The study introduces a qualitative insight into how system reliability and auditor independence shape whistleblowing behavior in educational and corporate institutions. Implications: Enhancing whistleblowing systems and auditor competence can improve fraud prevention effectiveness and organizational integrity. Highlights: Internal auditors perceive confidentiality as key to whistleblowing intention. Strong internal control fosters fraud detection and prevention. Leadership commitment sustains a secure ethical reporting culture. Keywords: Internal Auditor, Whistleblower Intention, Whistleblowing System, Internal Control, Fraud Prevention